2011
DOI: 10.1038/nature10424
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene correction of α1-antitrypsin deficiency in induced pluripotent stem cells

Abstract: Human induced pluripotent stem cells (hIPSCs) represent a unique opportunity for regenerative medicine since they offer the prospect of generating unlimited quantities of cells for autologous transplantation as a novel treatment for a broad range of disorders1,2,3,4. However, the use of hIPSCs in the context of genetically inherited human disease will require correction of disease-causing mutations in a manner that is fully compatible with clinical applications3,5. The methods currently available, such as homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
524
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 616 publications
(533 citation statements)
references
References 36 publications
3
524
0
4
Order By: Relevance
“…Utilizing a combined technology of zinc finger nucleases (ZFNs) and piggyBac, the authors efficiently corrected the pathogenic point mutation in patient iPSC. The normal metabolic function was restored in hepatocytes derived from corrected iPSC, which demonstrated in vivo functionality (Yusa et al, 2011). This study proved a concept that inherited liver metabolic disorder can be cured through gene correction.…”
Section: Human Ipsc Derived Hepatocytes For Cell Therapymentioning
confidence: 53%
See 1 more Smart Citation
“…Utilizing a combined technology of zinc finger nucleases (ZFNs) and piggyBac, the authors efficiently corrected the pathogenic point mutation in patient iPSC. The normal metabolic function was restored in hepatocytes derived from corrected iPSC, which demonstrated in vivo functionality (Yusa et al, 2011). This study proved a concept that inherited liver metabolic disorder can be cured through gene correction.…”
Section: Human Ipsc Derived Hepatocytes For Cell Therapymentioning
confidence: 53%
“…Yusa et al (2011) reported the targeted gene correction of α1-antitrypsin deficiency in human iPSC. Utilizing a combined technology of zinc finger nucleases (ZFNs) and piggyBac, the authors efficiently corrected the pathogenic point mutation in patient iPSC.…”
Section: Human Ipsc Derived Hepatocytes For Cell Therapymentioning
confidence: 99%
“…Besides the improved culture conditions, particularly the discovery of ROCK inhibitor-mediated clonal cell growth, there have been some major breakthroughs in our efforts to enhance the recombination rates. The development of zinc finger nuclease (ZFN) technology and, more recently, the transcription activator-like effector nuclease (TALEN) technology have allowed significant enhancement of gene targeting efficiency in iPSCs [28,29,[54][55][56][57][58]. These exciting new developments will no doubt have impact on the realization of iPSC potentials.…”
Section: Genetic Modifications In Ipscsmentioning
confidence: 99%
“…Moreover, even though the generated iPSCs and their derivatives bear certain mutations acquired during reprogramming, gene targeting and/or culture conditions, the mutations observed did not hamper the phenotypic correction in vivo, neither led to tumor formation. This work as well as several other reports published earlier this year highlight the need for exhaustive testing of iPSCs and their derivatives in the context of specific applications rather than absolute number of mutations acquired, i.e., iPSCs bearing mutations in genes compromising the function of differentiated cells should be discarded in favor of lines whose alterations do not hamper normal cell function upon differentiation and transplantation [13]. With these criteria in mind, one would rather prime functionality in a particular context instead of the absolute number of mutations observed.…”
mentioning
confidence: 99%
“…More recently, Yusa et al described the development of a novel gene targeting approach by combining the use of ZFN and piggyBAC transposon technology [13]. In their approach the authors were able to excise back the targeting construct from the host genome in the absence of the typical genomic scars induced by other commonly employed excisable methods such as the Cre-LoxP system.…”
mentioning
confidence: 99%